Expression - Wang-Xia Wang; Robert J. Danaher; Craig S. Miller; Joseph R. Berger; Vega G. Nubia; Bernard S. Wilfred; Janna H. Neltner; Christopher M. Norris; Peter T. Nelson (Genomics, Proteomics & Bioinformatics, 2014)
The miR-15/107 family comprises a group of 10 paralogous microRNAs (miRNAs), sharing a 5′ AGCAGC sequence. These miRNAs have overlapping targets. In order to characterize the expression of miR-15/107 family miRNAs, we employed customized TaqMan Low-Density micro-fluid PCR-array to investigate the expression of miR-15/107 family members, and other selected miRNAs, in 11 human tissues obtained at autopsy including the cerebral cortex, frontal cortex, primary visual cortex, thalamus, heart, lung, liver, kidney, spleen, stomach and skeletal muscle. miR-103, miR-195 and miR-497 were expressed at similar levels across various tissues, whereas miR-107 is enriched in brain samples. We also examined the expression patterns of evolutionarily conserved miR-15/107 miRNAs in three distinct primary rat brain cell preparations (enriched for cortical neurons, astrocytes and microglia, respectively). In primary cultures of rat brain cells, several members of the miR-15/107 family are enriched in neurons compared to other cell types in the central nervous system (CNS). In addition to mature miRNAs, we also examined the expression of precursors (pri-miRNAs). Our data suggested a generally poor correlation between the expression of mature miRNAs and their precursors. In summary, we provide a detailed study of the tissue and cell type-specific expression profile of this highly expressed and phylogenetically conserved family of miRNA genes.